Pengaruh Budaya Organisasi, Insentif Dan Motivasi Kerja Terhadap Kinerja Karyawan Studi Kasus Pada Lembaga Penyiaran Publik (LPP) Radio Republik Indonesia (RRI) Jakarta - Ramamukti, Surya Basudewo; Widjarnako, Wirawan; Sumantyo, Franciscus Dwikotjo Sri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the influence of organizational culture, incentives, and work motivation on employee performance at the Public Broadcasting Institution Radio Republik Indonesia (LPP RRI) Jakarta. A quantitative research approach was applied using a survey method, in which questionnaires were distributed to the entire population of 118 employees. Therefore, a saturated sampling technique was used. The collected data were analyzed using SPSS version 25, through several stages including validity and reliability testing, as well as classical assumption tests covering normality, multicollinearity, and heteroscedasticity. Multiple linear regression analysis was then conducted to determine the extent of influence of each variable. The findings indicate that organizational culture, incentives, and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. Hence, strengthening organizational values, implementing a fair incentive system, and enhancing employee motivation are strategic factors that can drive performance improvement within RRI. The results of this study are expected to serve as a reference for management in formulating policies to improve employee performance.